2006
DOI: 10.1007/s11120-005-9009-9
|View full text |Cite
|
Sign up to set email alerts
|

A photoacoustic method for rapid assessment of temperature effects on photosynthesis

Abstract: The photosynthetic and photoacoustic properties of leaf samples were studied using a photoacoustic system modified for precise temperature control. Data were collected over a temperature range of -10 degrees C to +60 degrees C. A distinct acoustic noise transient marked the freezing temperature of the samples. A positive absorption transient and a brief period of oxygen uptake marked the thermal denaturing temperature of the samples. Between these extremes, the effects of temperature on light absorption, oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Eventually, we study the effect of temperature on the conductivity of the FMO complex, which is differently one of the most effective factors on the transport properties of the system [83,84]. The variation of the conductivity rate for different temperatures is represented in figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, we study the effect of temperature on the conductivity of the FMO complex, which is differently one of the most effective factors on the transport properties of the system [83,84]. The variation of the conductivity rate for different temperatures is represented in figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…With the aid of powerful CO 2 lasers, the PA effect was successfully applied to study traces of different essential oils components within the plant tissues without the necessity for the later to be steam-distilled [12]. PA has showed high capabilities of being an alternative method for simultaneously measuring different photosynthetic parameters like light absorption, oxygen evolution and energy storage over a wide temperature range [13]. Recent studies showed that the technique was successfully applied to thermal characterization of ceramic tapes [10] and molecular relaxation effects in hydrogen chloride [14].…”
Section: Introductionmentioning
confidence: 99%
“…La amplitud de la señal fotoacústica es el resultado de llevar la sección irradiada de la hoja a su máximo rendimiento en el proceso de evolución del oxígeno y después saturarlo al irradiarla con la luz blanca continua, lo que afecta principalmente al fotosistema II (PS II)(Ducruet, et al, 2007;Moreno, et al, 2008). Esto induce una serie de cambios reversibles, como la absorción y el almacenamiento de fotones en los centros de reacción de las clorofilas, la continuidad de las cascadas de señalización y la hidrólisis del agua que tienen lugar en la membrana tilacoidal(Herbert, 2006;Järvi, et al, 2013).En todos los casos, ante el encendido y apagado de la luz blanca, el tiempo de respuesta de las plantas fue de aproximadamente tres segundos y la amplitud de la señal tuvo un cambio de alrededor de ± 6 µV, como se muestra en la figura 2a.En la figura 2b se observa el comportamiento en función del tiempo de la REO de las plantas infectadas con FOC y en las sanas, con una tendencia similar en las nubes de puntos correspondientes. Los valores de REO se estimaron a partir de la curva obtenida en cada medición y se expresaron como el porcentaje de caída de la señal fotoacústica al descontar la componente fotobárica mediante la saturación de la fotosíntesis.…”
unclassified